ANGGARAN PENJUALAN SEBAGAI DASAR PERENCANAAN KEUANGAN PADA PT. EURO P2P DIRECT INDO DI SAMARINDA - -, Lia Retnawati (EKONOMIA, 2014)
The purpose of this study was to determine whether the role of electronic sales budget kind of water purifier PT. Euro P2P Direct Indo in Samarinda has been effective or not effective as prepared on the basis of financial planning is a systematic sales budget in financial planning. Issues raised is whether the cause of the budget electronics sales at PT. Euro P2P Direct Indo in Samarinda not effective as a basis for financial planning. The financial planning PT. Euro P2P Direct Indo in Samarinda compiled from electronic sales budget in a systematic kind of water purifier effectively used, as seen from the budget of the electronic type of water purifier sales increased in May as seen from 145 units with a value Rp137.750.000, as of June 151 units with a value Rp143.450.000, as many as 158 units in July with a value Rp150.100.000, and in August as many as 164 units with a value Rp155.800.000, bringing the total sales of the electronic type water purifier during May to August 2014 amounting to Rp587.100.000. With electronic sales budget basic types of water purifier as the financial planning PT. Euro P2P Direct Indo during the month of May to August 2014 are used effectively, it can be seen from the budget electronics sales during May to August 2014 which have increased thus the hypothesis proposed in the writing of this study was rejected.